The Effect of the Deductive Method on Students’ Performance in Grammar in an SHS Classroom - Awute, Phidelia; Awute, Andreas; Kobla Ezuh, Sampson (International Journal of English Language Education, 2023)
The current study aims at investigating the effect of using deductive and inductive methods on students’ grammar in a Senior High School (SHS) in Ghana. It examines the effect of the deductive method on students’ performance in grammar and to find out the statistically significant difference between students taught using the deductive method and those taught using the inductive method. 100 students were chosen for the purpose of the study. There were two groups consisting of 50 students each. One of the groups is made up of the experimental while the other is the control group. The research instrument used is a pre-test and a post-test. The current study used quantitative approach to analyse data from control and experimental groups. Whereas the experimental group was taught using the deductive approach, the control group was taught through the inductive approach. Firstly, a pre-test was administered to both groups, after which the experimental group had a treatment stage lasting for four weeks. Data was collected and analysed through a t-test. The results of the analysis show significant differences between the means of the two groups of students’ scores in the post-test. The result is in favour of the experimental group (the group taught using the deductive approach of teaching). Findings revealed that there were differences in the mean grade point average of both groups, and statistically significant difference was observed. The questions that guided this study were: what is the effect of the use of the deductive method on students’ performance in grammar? And is there any statistically significant difference between students taught using the deductive method and those taught using the inductive method? There was, therefore, support for the research’s hypothesis. It was hypothesized that there is a good effect of the deductive method of teaching on students’ performance in grammar which resulted in the high performance of students in the experimental group.